2015
DOI: 10.1371/journal.pone.0132148
|View full text |Cite
|
Sign up to set email alerts
|

Cellular MicroRNA Let-7a Suppresses KSHV Replication through Targeting MAP4K4 Signaling Pathways

Abstract: BackgroundKaposi’s sarcoma (KS)-associated herpesvirus (KSHV) is the etiologic agent of KS, the most common AIDS-related malignancy. The majority of KS tumor cells harbor latent KSHV virus but only a small percentage undergoes spontaneous lytic replication. Viral reactivation from latency is crucial for the pathogenesis and development of KS, but the cellular mechanisms underlying the switch between viral latency and replication are not well understood.MethodsThe level of let-7 miRNAs and MAP4K4 in KSHV infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Tumors from both groups showed similar histology ( Figure 1—figure supplement 1 ) and MYC expression ( Figure 1I ). Gene-expression within tumors showed that previously validated let-7 targets involved in proliferation and growth including Cdc25a ( Johnson et al, 2007), Cdc34 ( Legesse-Miller et al, 2009 ), E2f2 ( Dong et al, 2010 ), E2f5 ( Kropp et al, 2015 ), and Map4k4 ( Tan et al, 2015 ) were upregulated in MYC -tumors, but suppressed back down to normal levels in the context of let-7 overexpression ( Figure 1J–L ), suggesting that the repression of these targets restrains MYC -dependent tumorigenesis. These data indicated that let-7g has potent tumor suppressor activity in the context of MYC -driven hepatoblastoma.…”
Section: Resultsmentioning
confidence: 90%
“…Tumors from both groups showed similar histology ( Figure 1—figure supplement 1 ) and MYC expression ( Figure 1I ). Gene-expression within tumors showed that previously validated let-7 targets involved in proliferation and growth including Cdc25a ( Johnson et al, 2007), Cdc34 ( Legesse-Miller et al, 2009 ), E2f2 ( Dong et al, 2010 ), E2f5 ( Kropp et al, 2015 ), and Map4k4 ( Tan et al, 2015 ) were upregulated in MYC -tumors, but suppressed back down to normal levels in the context of let-7 overexpression ( Figure 1J–L ), suggesting that the repression of these targets restrains MYC -dependent tumorigenesis. These data indicated that let-7g has potent tumor suppressor activity in the context of MYC -driven hepatoblastoma.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, MAP4K4 is the upstream regulator of the ERK, JNK, and p38 MAPK signaling pathways. MAP4K4 contains a let - 7 target site in its 3′-UTR, indicating that let-7 family can regulate MAPK pathways by altering MAP4K4 expression levels 39 , 40 . Hsa-let-7c-5p can facilitate human enterovirus 71 replication by inhibiting MAP4K4 expression; this mechanism might explain the virus’s ability to subvert the JNK pathway 41 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, let-7b have been reported to inhibit hepatitis C virus (HCV) infectivity by interacting with the HCV genome 37 . Let-7a suppresses Kaposi’s sarcoma-associated herpesvirus (KSHV) replication through targeting of MAP4K4 signaling pathways 38 . Let-7g inhibits hepatitis B virus (HBV) preS2 protein expression and generation of viral products 39 .…”
Section: Discussionmentioning
confidence: 99%